NITRILASES – AN ATTRACTIVE NITRILE DEGRADING BIOCATALYST - A. AGARWAL; V. K. NIGAM; A. S. VIDYARTHI (International Journal of Pharma and Bio Sciences, 2012)
Nitrile compounds are found everywhere in nature. They are synthesized naturally as well as xenobiotically. Nitrilases are nitrile degrading enzymes and belong to nitrilase superfamily. They convert nitriles into corresponding acids in a single step pathway. Members of this superfamily are present in both prokaryotes and eukaryotes and have characteristics αββα fold. They pose conserved Cysteine, Glutamate and lysine in catalytic triad and exist as inactive dimer and further oligomerize to become active. The enzyme is being used as an attractive biocatalyst for the production of fine chemicals and pharmaceuticals. Due to their high regioselectivity and enatioselectivity, the utility of nitrilases have progressed from the application of nitrilase in biotransformation to its importance in bioremediation. Nitrilases are also used in the treatment of toxic effluents, herbicides and in cyanide remediation. This review, gives large information about nitrilases and steps taken to improve the biotransformation potential of nitrilases.